Structure-guided stereoselectivity inversion of a short-chain dehydrogenase/reductase towards halogenated acetophenones. Issue 37 (18th April 2016) - Li, Aipeng; Ye, Lidan; Yang, Xiaohong; Yang, Chengcheng; Gu, Jiali; Yu, Hongwei
Abstract : The structure-guided rational design of an NADH-dependent short-chain dehydrogenase/reductase (SDR) reversed the stereoselectivity towards halogenated acetophenones from Prelog to anti-Prelog. Abstract : The structure-guided rational design of an NADH-dependent short-chain dehydrogenase/reductase (SDR) reversed the stereoselectivity towards halogenated acetophenones from Prelog to anti-Prelog. The enzyme–substrate interactions involving an aromatic ring and a halogen atom were proven to play critical roles in determining the stereoselectivity of these ketone reductions besides the steric repulsion.